2009
DOI: 10.1074/jbc.m803198200
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of O-GlcNAc Transferase with Glucose Deprivation in HepG2 Cells Is Mediated by Decreased Hexosamine Pathway Flux

Abstract: O-Linked N-acetylglucosamine (O-GlcNAc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
90
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 29 publications
12
90
0
Order By: Relevance
“…OGT and OGA mRNA expression increased, whereas OGA protein levels decreased and there was no change in OGT protein expression. Similar studies showed an increase in O-GlcNAc levels with glucose deprivation, while the changes in expression and activity of O-GlcNAc enzymes varied between different cell lines, suggesting the response is celltype dependent [36,37]. A rapid augmentation of O-GlcNAcylation with heat stress was reported, but there were no significant changes in the mRNA expression and activity of OGT, OGA, and the levels of UDP-GlcNAc [38].…”
Section: Mrna Expression Of the O-glcnac Cycling Enzymesmentioning
confidence: 66%
“…OGT and OGA mRNA expression increased, whereas OGA protein levels decreased and there was no change in OGT protein expression. Similar studies showed an increase in O-GlcNAc levels with glucose deprivation, while the changes in expression and activity of O-GlcNAc enzymes varied between different cell lines, suggesting the response is celltype dependent [36,37]. A rapid augmentation of O-GlcNAcylation with heat stress was reported, but there were no significant changes in the mRNA expression and activity of OGT, OGA, and the levels of UDP-GlcNAc [38].…”
Section: Mrna Expression Of the O-glcnac Cycling Enzymesmentioning
confidence: 66%
“…The recent reports (21,23,28) and the present study about increased O-GlcNAcylation under glucose deprivation are interesting in a more general sense because they demonstrate a high degree of diversity. The mechanism leading to increased O-GlcNAcylation under glucose deprivation not only seems to vary in a cell type but also in a metabolism-related manner, which suggests that further studies on the regulation O-GlcNAcylation are warranted because of its importance for cellular function.…”
Section: Discussionmentioning
confidence: 93%
“…Although certain details of the mechanism leading to increased O-GlcNAcylation upon glucose deprivation are now established (21,23,28), the origin of the UDP-GlcNAc required for increased O-GlcNAcylation is unknown. Our results indicate that glycogen provides an important source for the needed glucose because the inhibition of GP, the rate-limiting enzyme for glycogenolysis, prevented increased O-GlcNAcylation under glucose deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations